LEGAL AID AS SEEN IN THE LIGHT OF THE LAW NO. 270/2010 REGARDING THE AMENDMENT AND THE COMPLETION OF THE LAW NO. 51/1995 FOR THE ORGANIZATION AND THE PRACTICE OF THE LAWYER’S PROFESSION - STEFAN NAUBAUER (Challenges of the Knowledge Society)
According to the explanatory memorandum of the Government as well as to the favorable opinion of the Legislative Council, the Law no. 270/2010 relate mainly to the correlation the OUG no. 51/2008 on legal aid in civil matters, by covering in detail the circumstances and the conditions for granting legal aid as well as the organization of the activity of granting such assistance. From the perspective of European law, the Legislative Council appreciated that the new law is placed within the sphere of the legislation as regulated at the European Union level, that are circumscribed to the European Area of freedom, security and justice, within the European legislation reserved to the judicial cooperation in civil matters.In this material we will analyze the following issues: granting legal aid in criminal matters, in which defense is mandatory according to the dispositions in the Criminal Procedural Code; granting legal aid in any other causes except criminal ones, as modality to grant public legal aid, according to the law; legal aid throughout a lawyer, granted at the request of the organs of the local public administration; appointing the lawyer for legal aid; extra-judiciary legal aid; competences of the bars regarding legal aid; the department for the coordination of legal aid; services of legal aid; legal aid registry; payment for the activity of legal aid and extra-judiciary legal aid.